An exploration of fall-related, psychosocial variables in people with multiple sclerosis who have fallen. (October 2017) - Comber, Laura; Coote, Susan; Finlayson, Marcia; Galvin, Rose; Quinn, Gillian; Peterson, Elizabeth
Introduction: Psychosocial contributors to fall risk for people with multiple sclerosis are often overlooked in falls prevention practice. This study explored several fall-related, psychosocial variables and their association with falls self-efficacy in a sample of people with multiple sclerosis reporting a fall. Method: A cross-sectional, structured telephone survey was employed. The survey explored socio-demographics, multiple sclerosis characteristics, and fall-related psychosocial variables. Multiple linear regression was employed to investigate associations with Falls Efficacy Scale – International scores. Results: The mean Falls Efficacy Scale – International score for 140 participants was 38.14(SD = 10.16), and the mean Falls Control Scale score was 5.38(SD = 2.22). Fear of falling was expressed by 129 (92%) participants, with 111 (79%) reporting associated activity curtailment. A regression model including six predictors explained 47% of the variance in the Falls Efficacy Scale – International scores. Results of the multiple linear regression showed that fear of falling, associated activity curtailment, balance interference, falls control, and health status were associated with falls self-efficacy. Conclusion: Fear of falling and associated activity curtailment, low falls self-efficacy, and compromised falls control are common among people with multiple sclerosis who have fallen. These fall-related psychosocial variables are distinct and each warrants attention during assessment. Findings suggest that falls self-efficacy among people with multiple sclerosis who have fallen is a complex construct associated with physical and psychosocial factors.